1985
DOI: 10.1172/jci111777
|View full text |Cite
|
Sign up to set email alerts
|

Generation in plasma of a fast-acting inhibitor of plasminogen activator in response to endotoxin stimulation.

Abstract: Endotoxin producing bacteria cause disseminated intravascular coagulation (DIC); however, the mechanism of endotoxin action in man is still unclear. Impairment of the fibrinolytic system has been suggested as a contributing mechanism.A single injection of Escherichia coli lipopojysaccharide in rabbits resulted in a marked and prolonged increase of the levels of a fast-acting inhibitor of plasminogen activator (PAinhibitor) in plasma (from 3.9±0.7 to 41±13.2 U/ml after 3 h). Gel filtration studies indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
159
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(173 citation statements)
references
References 29 publications
13
159
0
1
Order By: Relevance
“…PAI-1 is a very potent and specific inhibitor of tissuetype plasminogen activator (t-PA) and urokinase [2,3], which rapidly inactivates t-PA in vivo [47]. Its exact physiopathological role in the regulation of in vivo fibrinolysis remains to be elucidated further [17, 18,481. PAI-1 has been isolated from several sources including bovine aorta endothelial cells [20] and several human tumor cell lines and cDNA has been expressed in E. coli and transiently in mammalian cells [5].…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 is a very potent and specific inhibitor of tissuetype plasminogen activator (t-PA) and urokinase [2,3], which rapidly inactivates t-PA in vivo [47]. Its exact physiopathological role in the regulation of in vivo fibrinolysis remains to be elucidated further [17, 18,481. PAI-1 has been isolated from several sources including bovine aorta endothelial cells [20] and several human tumor cell lines and cDNA has been expressed in E. coli and transiently in mammalian cells [5].…”
Section: Discussionmentioning
confidence: 99%
“…43 It has also been reported that ox-LDL facilitate the uptake of endotoxin by human endothelial cells. 42 The presence of endotoxin in our preparations is unlikely, since heating ox-LDL totally suppressed the increase of PAI-1 synthesis by HUVEC.…”
Section: Figure 2 Plots Of Effect Of Oxidized Low Density Lipoproteimentioning
confidence: 97%
“…43 While the effect of endotoxin is temperature-resistant, heating 50 /ig/ml ox-LDL protein for 15 minutes at 100°C completely suppressed the ability to stimulate PAI-1 synthesis, suggesting that endotoxin is not involved ( Table 2). This assumption is supported by the fact that no endotoxin was found with the Kabi-LAL endotoxin test.…”
Section: Effect Of Native and Oxidized Low Density Lipoproteins On Plmentioning
confidence: 99%
“…Clearance of PA-inhibitory activity from the circulation is rapid with measured half lives of 3.5 to 7 min (Colucci, Paramo et al 1985). Like other serpins, PAI-1 inhibits cognate proteases by mimicking their substrates, which results in the formation of an ester bond between the carboxyl group of serpin P1 residue and the hydroxyl group of the protease serine residue to produce a stable covalently linked inhibitor/protease inactive complex (De Taeye, ).…”
Section: Fast Acting Inhibitormentioning
confidence: 99%
“…A major source of PAI-1 is liver because it is an acute phase protein ). Clearance of PAinhibitory activity from circulation is also rapid with measured half lives of 3.5 to 7 min (Colucci, Paramo et al 1985). Even the PAI-1 that is not cleared from the circulation has a limited half life of about 1-2 h due to its spontaneous conversion to an inactive latent conformer in which some of the primary recognition residues are incorporated into its largest β sheet (Mottonen, Strand et al 1992).…”
Section: Introductionmentioning
confidence: 99%